Influencia de la capacitación de personal en el desempeño laboral de los trabajadores de Electro Oriente sede Iquitos, 2022 - Ñaupari Floridas, Flor Esperanza (2023)
The purpose of this research was to identify the influence of personnel training on the job performance of workers at the Electro Oriente company in the city of Iquitos. Use a pre-experimental design (without a control group) with an occasional simple sampling, which determines a sample made up of 105 company workers. The independent or treatment variable being the training of personnel, the same that was carried out during the year 2022 based on the company's training plan. The dependent variable, work performance, was measured as pre and post test, based on the official procedure of the company. The research hypothesis is that staff training positively influences job performance. The analysis of the data obtained shows that the average of the performance evaluation, on an evaluation scale that has a maximum of 100 points, improves after the training (from 90.86 to 92.04), however, according to the Wilcoxon statistical test. , the significance of this result is 0.507 with an alpha of 0.05, which does not allow accepting the research hypothesis, that is, that there is no statistical evidence that training positively and significantly influences the work performance of workers.